Transparência das informações públicas nos portais das instituições federais de educação profissional da região sul do Brasil - Faraco, Bruno Pereira (2015)
Considering the need of communication between public management and society and its citizens, in a way which is more effective and transparent, the aim of this research was to analyze the transparency of public information presented by the managers of the portals of southern Brazil’s Federal Institutes. It is a qualitative and quantitative research, applied as its purpose, and exploratory as its aim. In order to explain the issue from the theoretical frameworks published, it will be used as a procedure the bibliographic research and the further study field research in the six southern Brazil’s Federal Institutes. Therefore, the theoretical framework approaches aspects about public transparency, concepts of information and communication in the public sector, and it presents measurement indexes of public transparency. The data collection with the Institutes sought to measure – in the portals – the level of transparency of the information presented by the managers, applying a search tool which provided the transparency index of eleven categories of the researched items, besides verifying the presence of the required items by Access to Information Law. In the sequence, it sought to verify the Institutes managers’ perception of the aspects which composes the proposed theme, for the purpose of observing how the process of communication between public agencies and the citizen is happening. The main results obtained emphasize, in a general way, a low level of public information propagation, with a lower average of propagation to the information about social, environmental and economic responsibility, and a greater average to the information related to the institution’s general data – from its management structure to its ordinance. It was also observed that no institution which was researched fully comply with the demands of the Access of Information Law. The results about the manager perceptio demonstrate a tendency in publishing the produced information, however, elements such disorganization of information in the portals, lack of standardization of the virtual structure and type of language to use, and lack of procedures of popular participation and interaction in the portals are determiners to bring problems in the access and in the communication with the public. Besides, the short time of institutions’ creation and the short time of the managers assuming their functions must be considered as a reflex of the found results. Therewith, the present study highlighted the importance of Public Transparency theme and it reached a positive result to a scientific and social contribution.